GOOD CORPORATE GOVERNANCE DALAM MENINGKATKAN KEPUASAN MUZAKKI DI BADAN AMIL ZAKAT NASIONAL - Kuncaraningsih, Hana Septi; Ridla, Muhammad Rasyid (JURNAL MANAJEMEN DAKWAH, 2015)
This research is aimed to find empirical evidence the influence of Good Corporate Governance toward muzakki satisfaction on badan amil zakat nasional (BAZNAS) in Sleman-Yogyakarta. Good corporate governance is a concept that important to stakeholder, forming to make institutions free corruption, transparent, and professional. The research is uses quantitave approach. The data analysis using three tests of hypothesis, including rank spearman correlation coefficient, coefficient determination and simple linear regression. All hypothesis testing of the statement result in significant value. It can be concluded influence of Good Corporate Governance in positive and significant toward muzakki satisfaction, by the amount contributions of 16,3%. The research is expected to provide a new idea for a public institution to apply the concept of good corporate governance. Keywords: Good Corporate Governance, Muzakki Satisfaction, BAZNAS Sleman